Petit Atles Lingüístic del Domini Català [= PALDC], volum 9. - Luna-Batlle, Xavier (Zeitschrift für Katalanistik, 2024)
The article "Petit Atles Lingüístic del Domini Català [= PALDC], volume 9" by Joan Veny describes the ninth and final volume of the atlas, which was extracted from the extensive "Atles Lingüístic del Domini Català". The PALDC contains 250 linguistic maps representing phonetic, morphological, syntactic, and lexical aspects of the Catalan-speaking area. Joan Veny emphasizes the scientific accuracy and the importance of the PALDC as a resource for linguistics students and language enthusiasts.